The Impact of Maternal Knowledge on Dental Caries in Preschool Children - Luditha Dia Anggraeni; Sri Hidayati; Silvia Prasetyowati (International Journal of Advanced Health Science and Technology, 2025)
Dental caries remains one of the most prevalent oral health problems among preschool children, often linked to inadequate parental understanding of proper dental care. This study addresses the research problem of how maternal knowledge influences the occurrence of dental caries in preschool-aged children at PG/RA Muslimah NU Islamiyah Taman Sidoarjo. The aim was to determine whether maternal knowledge significantly correlates with children’s dental caries status. Using an analytical cross-sectional design, data were collected from 36 mother–child pairs selected through total sampling. Maternal knowledge was assessed using a structured questionnaire, while the children’s dental caries status was examined with a standardized dental health assessment sheet. Statistical analysis was conducted using the Chi-square test with Fisher’s test as the corrective alternative. The results showed that 47.2% of mothers possessed sufficient knowledge, while 50% of children exhibited low levels of dental caries. A significant relationship was found between maternal knowledge and dental caries prevalence (p = 0.001), indicating that higher maternal knowledge is associated with a lower incidence of caries in preschool children. These findings confirm that mothers play a central role in promoting healthy oral hygiene behaviors and reducing caries risk during early childhood. In conclusion, maternal knowledge exerts a substantial influence on children’s oral health outcomes, highlighting the need for targeted parental education and health promotion programs. Interventions that enhance mothers’ understanding of proper dental hygiene practices may contribute significantly to reducing dental caries prevalence in preschool populations. Strengthening oral health literacy among mothers is therefore recommended as a preventive strategy to support healthier dental development in young children.